2018
DOI: 10.2174/1566523218666180413150023
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of BDNF Gene Recombinant Mesenchymal Stem Cel ls and Adhesive Peptide-modified Hydrogel Scaffold for Spinal Cord Repa ir

Abstract: The study developed a promising implantation system for therapy of severe spinal cord injury and provided the first understanding of Screenfect® A about its functions on stem cell therapy for nerve tissue repair as well as three-dimentional gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Encapsulated BDNF-producing fibroblasts in alginate-poly- L -ornithine survived for at least one month after being transplanted into the site of cervical spinal cord injury in rats without immunosuppression [ 363 ]. Transfection of BDNF gene recombinant MSCs via the adhesive peptide PPFLMLLKGSTR-modified scaffold improved cell survival and BDNF expression [ 368 ]. Alginate-based compositions have also been used to transport NSCs-BDNF and BMSCs-BDNF, maintaining long-term survival and proliferation of cells, as well as controlled release of BDNF [ 362 ].…”
Section: Bdnf-targeting Strategies For Ad Modificationmentioning
confidence: 99%
“…Encapsulated BDNF-producing fibroblasts in alginate-poly- L -ornithine survived for at least one month after being transplanted into the site of cervical spinal cord injury in rats without immunosuppression [ 363 ]. Transfection of BDNF gene recombinant MSCs via the adhesive peptide PPFLMLLKGSTR-modified scaffold improved cell survival and BDNF expression [ 368 ]. Alginate-based compositions have also been used to transport NSCs-BDNF and BMSCs-BDNF, maintaining long-term survival and proliferation of cells, as well as controlled release of BDNF [ 362 ].…”
Section: Bdnf-targeting Strategies For Ad Modificationmentioning
confidence: 99%
“… Li et al (2018a) reported that the use of an HA scaffold modified with adhesive peptides for the treatment of SCI. MSCs with recombinant brain-derived neurotrophic factor exhibited improved cell survival and sustained gene expression in vitro .…”
Section: Stem Cells (Scs)mentioning
confidence: 99%
“…In a recent study, Li-Ming Li and colleagues applied a three-dimensional gene transfection technology by transfecting MSCs with brain derived neurotrophic factor (BDNF) gene using the liposomal gene carrier, ScreenFect ® A [129]. To improve gene expression as well as cellular survival after in vivo implantation of MSCs, an adhesive peptide (PPFLMLLKGSTR)-modified hydrogel scaffold was constructed using hyaluronic acid.…”
Section: Scaffoldsmentioning
confidence: 99%